Optimization of conditions for cryopreservation of isolated pear meristems in liquid nitrogen. (Experimental biology, 2015)
The effect of the duration of hardening of test-tube plants and thawing methods on growth recovery ofcryopreserved pear meristems was defined. Optimum hardening is 3-4 weeks with varying temperature and irradiance (8 h, at 22°C, with 7 μmol m-2s-1 irradiance, followed 16 h at -1°C without irradiance). The effect of different cryoprotectants on the viability of meristems after freezing in liquid nitrogen was studied. The best cryoprotectant for cryopreservation of isolated pear meristems is IBBR-1 (50% glycerol and 50% glucose). Recovering nutrient medium composition for regeneration in vitro cryopreserved pear meristems was developed.